Determining whether the effect of liraglutide on non‐alcoholic fatty liver disease depends on reductions in the body mass index. Issue 5 (30th June 2020) - Shiomi, Megumi; Tanaka, Yoichi; Takada, Tesshu; Otori, Katsuya
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) initially presents as steatosis, which can progress to non‐alcoholic steatohepatitis (NASH), and often presents clinically alongside metabolic syndromes. Glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) are regularly utilized to treat type 2 diabetes mellitus. The GLP‐1 RA—liraglutide—ameliorates liver enzymes, histological features, and liver fat content of patients with NASH. However, few studies have examined whether the effect of GLP‐1 RAs depends on changes in the patient's body mass index (BMI). Therefore, this retrospective study aimed to investigate whether the efficacy of liraglutide depended on the baseline BMI or a reduction in BMI. Methods: Fifty‐five Japanese patients with type 2 diabetes mellitus and NAFLD who received liraglutide treatment for 24 weeks were assessed. The association between BMI and liver function or fibrosis was evaluated based on the aspartate aminotransferase, alanine aminotransferase, and fibrosis‐4 indices. Results: We found that 24 weeks of liraglutide treatment improved liver function and fibrosis in patients with type 2 diabetes mellitus and NAFLD, regardless of BMI changes or obesity status. Conclusions: Our findings provide important insight into the impact of BMI on liver function and fibrosis in patients with type 2 diabetes mellitus and NAFLD who are treated with liraglutide. Abstract : This study aimed to determine whether the effect of liraglutide in improving nonalcoholic fatty liver disease (NAFLD) depended on the baseline body mass index (BMI) or a reduction in BMI. Baseline BMI and Δ BMI were not independent predictors of changes in liver function and fibrosis index. This study highlighted that 24 weeks of liraglutide treatment improved liver function and liver fibrosis in patients with type 2 diabetes and NAFLD, regardless of BMI change and obesity status.